MiR-27a-3p and miR-30b-5p inhibited-vitamin D receptor involved in the progression of tuberculosis - Xiao, Min; Yang, Song; Zhou, An; Li, Tongxin; Liu, Jingjing; Chen, Yang; Luo, Ya; Qian, Chunfang; Yang, Fuping; Tang, Bo; Li, Chunhua; Su, Na; et al. (Frontiers in Microbiology, 2022)
Background MicroRNAs (miRNAs) play a vital role in tuberculosis (TB). Vitamin D receptor (VDR), an miRNA target gene, and its ligand, vitamin D3 (VitD3), have been reported to exert protective effects against TB. However, whether miRNAs can affect the progression of TB by targeting VDR has not been reported. Materials and methods Research subjects were selected according to defined inclusion criteria. A clinical database of 360 samples was established, including the subjects’ demographic information, miRNA expression profiles and cellular experimental results. Two candidate miRNAs, miR-27a-3p, and miR-30b-5p, were identified by a high-throughput sequencing screen and validated by qRT–PCR assays. Univariate and multivariate statistical analyses were performed. VDR and NF-kB p65 protein levels were detected by Western blot assays. Proinflammatory cytokine expression levels were detected by enzyme-linked immunosorbent assay (ELISA). Luciferase assays and fluorescence-activated cell sorting (FACS) were further applied to elucidate the detailed mechanisms. Results Differential miRNA expression profiles were obtained, and miR-27a-3p and miR-30b-5p were highly expressed in patients with TB. These results showed that the two miRNAs were able to induce M1 macrophage differentiation and inhibit M2 macrophage differentiation. Further experiments showed that the two miRNAs decreased the VDR protein level and increased proinflammatory cytokine secretion by macrophages. Mechanistically, the miRNAs targeted the 3′ untranslated region (3′UTR) of the VDR mRNA and thereby downregulated VDR protein levels by post-transcriptional regulation. Then, due to the reduction in VDR protein levels, the NF-kB inflammatory cytokine signaling pathway was activated, thus promoting the progression of TB. Conclusion Our study not only identified differentially expressed miRNAs between the TB and control groups but also revealed that miR-27a-3p and miR-30b-5p regulate proinflammatory cytokine secretion and macrophage differentiation through VDR in macrophages. Thus, these two miRNAs influence the progression of TB.